2010
DOI: 10.1124/jpet.110.169243
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD38, a Cyclic ADP-Ribosylcyclase, in Morphine Antinociception and Tolerance

Abstract: Our previous studies have demonstrated that an increase in intracellular levels of Ca 2ϩ in neurons is an important component of both the antinociception produced by morphine and morphine's tolerance. The present study tested the hypothesis that the Ca 2ϩ signaling second messenger, cyclic ADP-ribose (cADPR), derived from CD38 activation participates in morphine antinociception and tolerance. We first showed that morphine's antinociceptive potency was increased by the intracerebroventricular injection of CD38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, Sadeghi et al found that phenytoin may inhibit Ca2+ influx through regulate cyclase activity of CD38 and cADPR (cyclic adenosine diphosphate ribose), and then play an anticonvulsant role in the treatment of depression (33). Hull et al found that CD38 may be involved in morphine tolerance and pain receptor abnormalities by regulating CD38-cADPR-ryanodine receptor Ca (2+) signalling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sadeghi et al found that phenytoin may inhibit Ca2+ influx through regulate cyclase activity of CD38 and cADPR (cyclic adenosine diphosphate ribose), and then play an anticonvulsant role in the treatment of depression (33). Hull et al found that CD38 may be involved in morphine tolerance and pain receptor abnormalities by regulating CD38-cADPR-ryanodine receptor Ca (2+) signalling pathway (34).…”
Section: Discussionmentioning
confidence: 99%